Sustainable Energy Resources and Economics in Iceland and Greenland - Kristjánsdóttir, Helga (Springer eBooks, 2015)
This book provides fascinating examples of the ways renewable and sustainable energy can support economic growth, which will be illuminating for academic researchers and students, as well as those interested in green investment opportunities.The distinctive glacial, volcanic and oceanic environments of Iceland and Greenland supply abundant renewable energy resources in the form of hydropower and geothermal energy. As one of the few nations in the world with 100% renewable electricity production, Iceland is a compelling case study of a sustainable energy driven economy. Consideration of Greenland provides an interesting contrast, as its enormous potential for hydropower scale-up has only been minimally harnessed. The variable and fixed cost factors governing further expansion and export of the regions' sustainable power via sub-sea cable are detailed.